Thaneermukkom salt water barrier to prevent salt water intrusion: An overview of kuttanad low land development - Sitharam, Thallak. G. (IAHR, 2020)
The Thaneermukkom salt water barrier bund was constructed in 1974 to prevent tidal action and intrusion of salt water into the Kuttanad low land across the Vembanad Lake in Kerala, India. This bund divides the Vembanad lake into two, Thaneermukkom in the south with fresh water fed by the rivers draining into the lake and Vechur in the north with brackish water fed by the Arabian Sea. This bund creates a fresh water storage reservoir by storing river flood water, which has helped the farmers in Kuttanad, where farming occurs below sea level. The gates of the bund are opened during the monsoon period and are closed after approximately six months. This article reviews the present status of the Thaneermukkom reservoir and provides suggestions for tackling its environmental and ecological problems such as the pollution of the backwaters and the entire land nearby and the rampant hyacinth growth in the freshwater reservoir.